Towards Achieving Substantive Justice: The Importance of Extending the Time Limit for Resolving Presidential Election Disputes - Bunga Kharisma; I Gde Sandy Satria (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2024)
Presidential election dispute resolution (PHPU) is complicated because its scope covers the entire territory of Indonesia and its application to Indonesian citizens in various parts of the world. The PHPU dispute resolution process must also guarantee maximum protection of constitutional rights. This research uses normative research methods using secondary data sources. This aims to assess the urgency of extending the deadline for resolving presidential election disputes, which is currently 14 working days from the date of submission. Research sculpture approach and conceptual approach. These findings illustrate the need for changes to legislation to extend the time limit for resolving PHPU disputes beyond the existing 14-day limit. In practice, this time period does not provide maximum opportunity for the presentation of evidence. Historical analysis shows that from the 2004 presidential election to 2024, not a single PHPU demand has been granted, mainly because the demand cannot be proven. The author emphasizes that a time limit that is too early does not guarantee substantive justice, which includes not only fair and accurate decision-making, so rational considerations are needed that produce rational and logical decisions and a process that allows each party to present their arguments comprehensively and obtain fair treatment in the judicial process.